1994
DOI: 10.1177/004051759406400802
|View full text |Cite
|
Sign up to set email alerts
|

Shrink-Resistant Properties and Surface Characteristics of Wool Fibers Treated with Multifunctional Epoxides

Abstract: Shrink-resistant properties and surface characteristics were investigated for wool fibers treated with hydrophilic multifunctional epoxides (glycerol polyglycidyl ether—GPE). Two different reaction conditions were used for the treatment, one in a saturated NaCl aqueous solution (S sample ) and the other in the absence of NaCl (W sample). Addon percentages of both samples were almost the same. On the other hand, both shrink-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The protease-treated and S-BAP+S-RPU combination finished fabric (9.44%) is shrunk lesser than other combination finished fabrics (> 10.34%). The deposition of S-BAP polymer on the modified cuticle layer followed by masking the scales of the wool fibers and improvement in hydrophilicity by S-RPU polymer may reduce synergistically the differential friction effect of the wool fibers and alternatively reduces the shrinkage this blend fabric 25,26) . Ⅰ6ⅠL.…”
Section: Shrinkagementioning
confidence: 99%
“…The protease-treated and S-BAP+S-RPU combination finished fabric (9.44%) is shrunk lesser than other combination finished fabrics (> 10.34%). The deposition of S-BAP polymer on the modified cuticle layer followed by masking the scales of the wool fibers and improvement in hydrophilicity by S-RPU polymer may reduce synergistically the differential friction effect of the wool fibers and alternatively reduces the shrinkage this blend fabric 25,26) . Ⅰ6ⅠL.…”
Section: Shrinkagementioning
confidence: 99%
“…Previous investigations of air permeability considered airflow through many diverse substrates such as parachute cloths, nets, gauzes, apparel fabrics, etc. These studies [4,1] ] changed elements of fabric structures and reported the effects on the airflow rate when a relatively low pressure drop was applied. However, little published work is available that is specific to the high pressure projection of gas through textile structures, which is akin to the functional performance of an airbag.…”
Section: Literature Citedmentioning
confidence: 99%
“…Multifunctional epoxides react with protein fibers such as wool and silk. The epoxides crosslink with amino acid residues, e.g., amines, alcohols, phenols, thiols, carboxylic acids, and so on, thus improving such fabric performance properties as shrink resistance and wrinkle recovery [4,12,18,23 ] . Many researchers have analyzed the reactivity of epoxide on silk and demonstrated its effects with regard to changes in physical properties, moisture absorption, chemical resistance, and wash and wear properties [20,22,26].…”
mentioning
confidence: 99%
“…The chemical modification of wool can be regarded as a powerful tool to improve some inferior textile performance of the fibers and to impart new physico‐chemical and functional properties suitable for technological implementation, in order to meet market requirements for better wear and maintenance behavior of textile goods and for developing new textile products. The most popular chemical modification techniques are the graft copolymerization of vinyl monomers,1, 2 and the reaction of modifying agents, such as epoxides3–6 and acid anhydrides 7–9. Grafting implies the loading of fibers with large amounts of polymer, which are often needed to obtain the desired effect.…”
Section: Introductionmentioning
confidence: 99%
“…The first attempts to apply epoxides date back to the 1970s, thanks to the scientific contribution of Tanaka and Shiozaki 3. Epoxide‐treated wool fibers exhibited improved chemical resistance,3 crease recovery,5 and shrink‐resist properties 6. However, in spite of the evident improvement of fiber properties, the application to industrial‐scale processing of the epoxide treatment is still limited.…”
Section: Introductionmentioning
confidence: 99%